Microstructure and tribocorrosion properties of NiTi/AlNi2Ti ternary intermetallic alloy. (February 2021) - Chen, H.; Zhang, Z.; Hao, X.H.; Huang, B.X.; Zhao, X.C.; Hu, C.C.
Abstract: NiTi/AlNi2 Ti intermetallic alloy consisting of AlNi2 Ti primary dendrites and NiTi interdendritic phase was fabricated by arc melting process. Tribocorrosion behaviors of the alloy in 0.5 mol/L H2 SO4 solutions were characterized using tribocorrosion tests and X-ray photoelectron spectroscopy (XPS). Corrosion-wear synergistic effect and tribocorrosion mechanism were also discussed. The tribocorrosion test results showed that the open circuit potential (OCP) of NiTi/AlNi2 Ti alloy decreases and the corrosion current density increases as the sliding starts, and the decrease in the OCP value is proportional to the increase in the frictional force, indicating a strong corrosion-wear synergistic effect. The NiTi/AlNi2 Ti alloy has better tribocorrosion resistance than the 0Cr18Ni9 material in 0.5 mol/L H2 SO4 solution with a high OCP, low corrosion current and low wear volume. The wear volume of NiTi/AlNi2 Ti alloy is about 10 times lower than that of reference material 0Cr18Ni9. The calculation results of materials loss (ΔV) during tribocorrosion test indicated that corrosion accelerated wear (Vcw ) was the main corrosion-wear synergistic mechanism. Highlights: NiTi/AlNi2 Ti intermetallic alloy was fabricated by vacuum arc melting process. The alloy exhibits a strong wear-corrosion synergistic effect in H2 SO4 solutions. The NiTi/AlNi2 Ti alloy has better tribocorrosion resistance than the 0Cr18Ni9 material. Corrosion accelerated wear (Vcw ) was the main wear-corrosion synergistic mechanism.